Geo-Climatic Changes and Apomixis as Major Drivers of Diversification in the Mediterranean Sea Lavenders (Limonium Mill.) - Koutroumpa, Konstantina; Warren, Ben H.; Theodoridis, Spyros; Coiro, Mario; Romeiras, Maria M.; Jiménez, Ares; Conti, Elena (Frontiers in Plant Science, 2021)
The Mediterranean realm, comprising the Mediterranean and Macaronesian regions, has long been recognized as one of the world’s biodiversity hotspots, owing to its remarkable species richness and endemism. Several hypotheses on biotic and abiotic drivers of species diversification in the region have been often proposed but rarely tested in an explicit phylogenetic framework. Here, we investigate the impact of both species-intrinsic and -extrinsic factors on diversification in the species-rich, cosmopolitan Limonium, an angiosperm genus with center of diversity in the Mediterranean. First, we infer and time-calibrate the largest Limonium phylogeny to date. We then estimate ancestral ranges and diversification dynamics at both global and regional scales. At the global scale, we test whether the identified shifts in diversification rates are linked to specific geological and/or climatic events in the Mediterranean area and/or asexual reproduction (apomixis). Our results support a late Paleogene origin in the proto-Mediterranean area for Limonium, followed by extensive in situ diversification in the Mediterranean region during the late Miocene, Pliocene and Pleistocene. We found significant increases of diversification rates in the ‘Mediterranean lineage’ associated with the Messinian Salinity Crisis, onset of Mediterranean climate, Plio-Pleistocene sea-level fluctuations, and apomixis. Additionally, the Euro-Mediterranean area acted as the major source of species dispersals to the surrounding areas. At the regional scale, we infer the biogeographic origins of insular endemics in the oceanic archipelagos of Macaronesia, and test whether woodiness in the Canarian Nobiles clade is a derived trait linked to insular life and a biotic driver of diversification. We find that Limonium species diversity on the Canary Islands and Cape Verde archipelagos is the product of multiple colonization events followed by in situ diversification, and that woodiness of the Canarian endemics is indeed a derived trait but is not associated with a significant shift to higher diversification rates. Our study expands knowledge on how the interaction between abiotic and biotic drivers shape the uneven distribution of species diversity across taxonomic and geographical scales.